A Public Sector Innovation: Determinants analysis of sustainability for Examining the Role of User Impact Mediation in the Dolan Banyumas Application - Suci Lestari; Tobirin; Arif Muhamad Nurdin; Siti Balqis Huriyah (PT ARRUS Intelektual Indonesia, 2026)
This study examines the determinants of sustainability of public sector innovation by examining the mediating role of user innovation impact in the Dolan Banyumas application. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). Data was collected through an online survey of 60 respondents who used the Dolan Banyumas application who were selected using the purposive sampling technique. The research model examines the relationship between three main constructs, namely the perception of innovation novelty, the impact of innovation, and the sustainability of innovation. The results of the study show that the perception of innovation novelty has a positive and significant effect on the impact of innovation and the sustainability of innovation. In addition, the impact of innovation has been shown to have a significant effect on the sustainability of innovation and effectively mediates the relationship between the perception of innovation novelty and innovation sustainability. The value of the determination coefficient shows that this research model is able to explain 73.9% variation in innovation impact and 73% variation in innovation sustainability. The main findings of this study show that the sustainability of digital innovation in the public sector is not only determined by the aspect of technological novelty alone, but is highly dependent on the benefits or real impacts that are directly felt by service users. Keywords: Public Sector Innovation, Digital Governance, Innovation Sustainability, Innovation Impact, SEM-PLS.